The Effect of Jaloh (Salix tetrasperma Roxb) Extract on Fat level and Water Content in muscle of Broiler Chicken which Heat Stres Condition - Yana Zein; Sugito Sugito; Amiruddin Amiruddin; Roslizawaty Roslizawaty; Gholib Gholib; M. Isa (Universitas Syiah Kuala, 2023)
Exposure to heat conditions is one of the causes of heat stress for broilers. This research was conducted to determine the effect of administering jaloh extract (Salix tetrasperma Roxb) in drinking water to broiler chickens with heat stress condition on fat levels and muscle water content (intramuscular). This research was conducted using a completely randomized design with a sample of 15 broiler chickens strain MB 90 aged 21 days which placed in individual cages and a temperature of 34 ± 1ºC was set for 4 hours/day for 7 consecutive days. The treatment groups were as follows: P0 as control group without jaloh extract; P1 was given jaloh extract at a dose of 50 mg/l; P2 was given jaloh extract at a dose of 100 mg/l in drinking water. Each treatment group consisted of 5 replications. The data were analyzed using ANOVA test, and then continued with the Duncan test. The results showed that jaloh extract at a dose of 100 mg/l in drinking water could increase the fat content of meat up to 16.63% and could reduce the water content to 44.52%. It could be concluded that the administration of jaloh extract at a dose of 100 mg/l in drinking water could increase fat levels and reduce intramuscular muscle water content in broiler chickens with heat stress condition